La Tecnología como Estrategia Didáctica en el Fortalecimiento de los Procesos Lecto Escriturales en los Estudiantes de Tercero De Primaria del Colegio Alegría Del Niño del Distrito Riohacha (2022)
Taking into account what was affirmed by the Ministry of Higher Education (MEN), where it ratifies that through technologies, significant learning can be developed and promote the different teaching processes. In this sense, the present monographic work, Technology as a Didactic Strategy in the Strengthening of Literacy Processes, aimed at students in the third grade of elementary school of the Alegría del Niño School, which proposes a perceptual methodology, which from the observation, allowed me to know some difficulties in the reading processes- and writing, also carry out a diagnosis, of what use they were giving to the tools technologies in the development of reading and writing skills in the process. The development of this research occurred during the planning and execution of three practices teachers, which were directed to implement a strategy that would contribute to improve reading and writing processes, in order to train competent students with a critical level and thoughtful. Furthermore, considering that reading and writing skills influence their development and in all areas of knowledge. It should be noted that technology as a didactic strategy marks an important place in this time for the different changes that education has brought. Which makes it possible to demonstrate importance in the academic processes of the students. Initially, the realities of the educational context of the institution were identified through the observation of the different difficulties that students have in the development of habits literacy. Then, determine the strategy that would serve as support in the 13 strengthening of these processes. Adding to this the universal situation that the world experienced with the COVID-19 pandemic; has been one of the additional factors to the problem already raised, the quarantine measures and other restrictions that have characterized these times of pandemic have necessarily included the implementation of some changes in the dynamics of the daily learning. As a teacher in training, she managed to develop at the Alegría del Niño school; the three teaching practices programmed by the university, which allowed evidence from the observation, the different academic activities carried out by the children; they were missing one didactic component that will help them make their process and learning more effective through motivating teaching strategies. What leads to students feeling motivated to achieve significant learning, especially in relation to reading and writing, essential factors in academic progress and in the results achieved, both in internal and external tests that measure the quality of the institution's education. Thus, during the teaching practices, it was possible to show that the tools technological, are proposed as an alternative to help the teacher in his classes since It allows to represent and apply a number of materials for all areas of knowledge. Similarly, to develop different skills in students, since it is very importance of reading and writing, in all the activities they carry out, so that they are competent with analytical thinking, allowing you to successfully finish the school year, as well as It is the responsibility of the counselor to be at the forefront to implement strategies in the teaching – learning. It is worth mentioning that the teaching practices were developed following the model Constructivist pedagogical approach adopted by the school. Which, served as support to nurture the present 14 monographic work and that when working with the proposed technological tools, served as a didactic component. Obtaining satisfactory results without neglecting the area plans that have been implemented in the school.